ANALISIS BLENDED LEARNING DALAM PENINGKATAN MOTIVASI BELAJAR SISWA DI SD - Abroto; Seka Andrean; Aulia Diana Devi (ABDAU : Jurnal Pendidikan Madrasah Ibtidaiyah, 2021)
Along with the development of science and technology requires teachers to make an innovation in teaching and learning activities, one of which is by using strategies and learning models. The purpose of this study is to describe the use of blended learning methods in improving students' learning motivation. The method used is the library research approach through library resources related to blended learning methods in improving learning motivation as well as various other literature sources. Then analyzed and presented the findings of the data objectively. The results showed that Blended Learning is a learning that combines conventional learning, self-learning and online self-learning. In improving learning motivation with Blended Learning method in elementary school can be done with several steps, namely 1) preparing the syllabus and Learning Program Plan (RPP), 2) making a draft assessment 3) determining suitable methods, and 4) implementing the learning process that takes place effectively. With this, the teaching and learning process can take place well and produce an educated generation, who are able to compete and answer future challenges, as well as excel.